2017
DOI: 10.1002/jor.23451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of platelet-rich plasma on degeneration change of rotator cuff muscles: In vitro and in vivo evaluations

Abstract: Atrophy with fatty degeneration is often seen in rotator cuff muscles with torn tendons. PRP has been reported to enhance tissue repair processes after tendon ruptures. However, the effect of PRP on atrophy and fatty degeneration of the muscle is not yet known. The aim of this study is to examine the effect of PRP on degeneration change of rotator cuff muscles in vitro and in vivo. A murine myogenic cell line and a rat rotator cuff tear model were used in this study and PRP was administrated into subacromial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
1
16
1
Order By: Relevance
“…Variable levels of differentiation have been reported for different cell types, for example increased differentiation for rat bone marrow cells, human skeletal muscle myoblasts, rat muscle satellite cells, rabbit bone marrow mesenchymal stem cells and C2C12 myoblasts or maintained effect with hMDPCs, myo‐endothelial cells and pericytes compared to control conditions . Conversely, some studies reported that platelets inhibited differentiation of C2C12 myoblasts . This discrepancy in the current literature may provide the basis for a thorough consideration of the technical aspects in platelet applications that may affect the final outcome in a study.…”
Section: Platelet‐mediated Skeletal Muscle Regenerationmentioning
confidence: 97%
See 2 more Smart Citations
“…Variable levels of differentiation have been reported for different cell types, for example increased differentiation for rat bone marrow cells, human skeletal muscle myoblasts, rat muscle satellite cells, rabbit bone marrow mesenchymal stem cells and C2C12 myoblasts or maintained effect with hMDPCs, myo‐endothelial cells and pericytes compared to control conditions . Conversely, some studies reported that platelets inhibited differentiation of C2C12 myoblasts . This discrepancy in the current literature may provide the basis for a thorough consideration of the technical aspects in platelet applications that may affect the final outcome in a study.…”
Section: Platelet‐mediated Skeletal Muscle Regenerationmentioning
confidence: 97%
“…Studies now emerging are finding beneficial results with platelet releasate in muscle regeneration similar to PRP treatments . One crucial and recent study added platelet releasate to a primary culture of rat gastrocnemius muscle cells with the aim of investigating the impact of releasate on cell proliferation .…”
Section: Platelet‐mediated Skeletal Muscle Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…PRP has been known to stimulate both the response of mesenchymal stem cells (MSCs) to the local area through growth factors such as plateletderived growth factor (PDGF), fibroblast growth factor and vascular endothelial growth factor (VEGF) and stimulate tendon stem cells to differentiate into tenocytes when certain growth factors are released, which promotes healing of the rotator cuff [67,68]. Furthermore, PRP can also assist in the proliferation of muscle cells [69], promoting inflammation [70], and the use of adhesion molecules to repair the torn tendon [71]. The proliferation of muscle cells allows for an increased number of fibroblasts and myotubes, thereby decreasing the overall time of recovery and increasing the strength of the rotator cuff [69].…”
Section: Basic Sciencementioning
confidence: 99%
“…Furthermore, PRP can also assist in the proliferation of muscle cells [69], promoting inflammation [70], and the use of adhesion molecules to repair the torn tendon [71]. The proliferation of muscle cells allows for an increased number of fibroblasts and myotubes, thereby decreasing the overall time of recovery and increasing the strength of the rotator cuff [69]. Non-growth factors released from platelets such as serotonin, histamine, dopamine, calcium and adenosine aid in inflammation proliferation [70].…”
Section: Basic Sciencementioning
confidence: 99%